2018
DOI: 10.3384/lic.diva-153100
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Fatigue Behaviour of Austenitic Stainless Steel : Influence of Ageing on Thermomechanical Fatigue and Creep-Fatigue Interaction

Abstract: The global energy consumption is increasing and together with global warming from greenhouse gas emission, create the need for more environmental friendly energy production processes. Higher efficiency of biomass power plants can be achieved by increasing temperature and pressure in the boiler section and this would increase the generation of electricity along with the reduction in emission of greenhouse gases e.g. CO 2. The power generation must also be flexible to be able to follow the demands of the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…One of softening manifestations is the sigmoidal hysteresis loops ( Figure 7 ), rather than symmetric loops [ 31 ], where de-twining is most probably due to the activity of partial dislocations. Additionally, the unique orientation relationship between the parent grains and the twin grains favors de-twining during loading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of softening manifestations is the sigmoidal hysteresis loops ( Figure 7 ), rather than symmetric loops [ 31 ], where de-twining is most probably due to the activity of partial dislocations. Additionally, the unique orientation relationship between the parent grains and the twin grains favors de-twining during loading.…”
Section: Resultsmentioning
confidence: 99%
“…In short, in hold time tests such as the 60 s hold time ( Figure 7 a), more than one cycle was needed to cause material softening and shift to the negative strain regime, as mentioned above. Wärner [ 31 ] studied the high-temperature fatigue of austenitic stainless steels, and found that dynamic recrystallization can occur if a certain critical strain is reached. The number of cycles needed to reach this critical strain depends on the dwell time applied in each test.…”
Section: Resultsmentioning
confidence: 99%
“…For safety reasons, the effect of prolonged microstructural degradation is also investigated to evaluate the durability of the materials. More specifically, the following research questions (RQ) have been addressed: [28] which was presented in December 2018. However, the content has been significantly modified and extended since then.…”
Section: Research Questionsmentioning
confidence: 99%
“…First, the toughness of the material should be improved to resist the impact load, such as using carburised steel [34]. Second, the surface damage and the probability of crack occurrence can be reduced by coatings [94,95], especially in the case with roll-slip phenomenon. Finally, reducing inclusions in steel, especially those that induce WECs easily, can inhibit the occurrence of early fatigue.…”
Section: Microstructural Alterationmentioning
confidence: 99%